Community assembly of microbial habitat generalists and specialists in urban aquatic ecosystems explained more by habitat type than pollution gradient. (15th July 2022) - Abdullah Al, Mamun; Xue, Yuanyuan; Xiao, Peng; Xu, Jing; Chen, Huihuang; Mo, Yuanyuan; Shimeta, Jeff; Yang, Jun
Highlights: The habitat influence is stronger than pollution on microbial community structure. Environmental influence on microbial communities was stronger in water than in sediment. Different mechanisms identified in shaping generalists and specialists in water and sediment. Microbial community showed stronger distance-decay in sediment than in water. Microeukaryotic habitat specialists could be keystone in microbial co-occurrence network. Abstract: Urban freshwater ecosystems have important ecosystem functions, provide habitats for diverse microbial communities and are susceptible to multiple interconnected factors such as environmental pollution. Despite the ecological significance of bacteria and microeukaryotes, little is known about how their community assembly responds to various environmental factors across water and sediment habitats and ecological processes shaping them. Here, environmental DNA-based approaches were used to investigate the community assembly processes of bacteria and microeukaryotes (including habitat generalists and specialists) in urban water and sediment across an urban-pollution gradient in Wuhan, central China. The diversity, community composition and potential function of bacteria and microeukaryotes showed significantly stronger variation between water and sediment than across an urban pollution gradient. Although, bacterial and microeukaryotic community assemblies were dominated by strong selection processes in both water and sediment habitats, but a contrasting community assembly mechanism was identified between habitat generalists and specialists. Bacterial and microeukaryotic communities showed a greater response to physicochemical variability in water, while a strong distance-decay relationship was found in sediment. Further, cross-kingdom microbial network analysis revealed strong modular associations of bacteria and microeukaryotes, meanwhile, microeukaryotic habitat specialists might be keystone, but generalists have higher proportion of connections in the networks. This study provides significant insights into the response of bacteria and microeukaryotes to different urban pollutions between water and sediment, and the ecological processes structuring microbial community dynamics across habitat types under anthropogenic disturbances. Graphical abstract: Image, graphical abstract